co-activator of nitrogen-regulated transcription in Saccharomyces cerevisiae - Soussi-Boudekou, S; Andre, B (Molecular microbiology, 1999)
In Saccharomyces cerevisiae, the transcription factors Gln3p and Nil1p of the GATA family play a determinant role in expression of genes that are subject to nitrogen catabolite repression. Here we report the isolation of a new yeast mutant, gan1‐1, exhibiting dramatically decreased NAD‐linked glutamate dehydrogenase (NAD‐GDH) and glutamine synthetase (GS) activities. The GAN1 gene was cloned and found to encode a 488‐amino‐acid polypeptide bearing no typical DNA binding domain. Gan1p is required for full expression of GLN1, GDH2 and also other nitrogen utilization genes, including GAP1, PUT4, MEP2 and GDH1. The extent to which Gan1p is required, however, varies according to the gene and to the nitrogen source available. We show that Gan1p is in fact involved in Gln3p‐ and Nil1p‐dependent transcription. In the case of Gln3p‐dependent transcription, the degree to which Gan1p is required appears to be gene specific. The contribution of Gan1p to gene expression is also influenced by the nitrogen status of the cell. We found that GAN1 is identical to ADA1, which encodes a component of the ADA/GCN5 co‐activator complex. Ada1/Gan1p thus represents the first reported case of an accessory protein (a co‐activator) linking the GATA‐binding proteins Gln3p and Nil1p, mediating nitrogen‐regulated transcription, to the basal transcription machinery.